Telemedicina em maternidade terciária no Ceará: satisfação das usuárias e desafios na implementação - Rodrigues, Renata Cunha Lima (2024)
Telemedicine enables healthcare using information and communication technologies to exchange valid information for diagnosis, prevention and treatment of diseases. Teleconsultations have evolved in degree and number, especially since the COVID-19 pandemic, in order to reduce the movement of people. At the Assis Chateaubriand Maternity School (MEAC), telemedicine care has begun since the pandemic. The aim of this study was to assess the challenges faced in implementing the telemedicine service at MEAC, as well as to analyze the satisfaction of the patients treated there. We carried out a descriptive observational cross-sectional study with the participation of patients seen between 2020 and 2023, via telephone or video calls and documented in electronic medical records. Online questionnaires were sent to all patients seen in 2021 and 2023. Variables such as age, income, origin, reason for follow-up, waiting time for the appointment, absenteeism were evaluated, as well as the satisfaction of the women seen using the questionnaire "Avaliação da Satisfação de Pacientes Atendidos via Telemedicina (QASTele)", validated in Portuguese, and the main difficulties observed in carrying out medical consultations in this modality. We obtained 71 responses from 71 patients. The average age of the patients was 43.9 years, and most of them came from Fortaleza. 33 participants were single (46.5%) and 69% had a family income of less than one minimum wage. 53.5% of the participants reported full satisfaction with the telemedicine service, with difficulty in accessing the internet signal being a significant factor of dissatisfaction in the univariate analysis (p=0.040). Some limitations were the difficulty in acquiring answers from the participants, as well as their adequate access to digital tools. More studies needed to compare the profile of care and satisfaction in order to improve telemedicine care for gynecology and obstetrics patients.